2012
DOI: 10.1111/j.1365-2613.2012.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages in healing the wounded lung

Abstract: SUMMARYAcute tissue injury is often considered in the context of a wound. The host response to wounding is an orchestrated series of events, the fundamentals of which are preserved across all multicellular organisms. In the human lung, there are a myriad of causes of injury, but only a limited number of consequences: complete resolution, persistent and/or overwhelming inflammation, a combination of resolution/remodelling with fibrosis or progressive fibrosis. In all cases where complete resolution does not occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 77 publications
2
53
0
2
Order By: Relevance
“…Recently, miR-155, a distinct miRNA molecule, was found to have an important role in inflammatory and immune response (17,19). Moreover, miR-155 also was found upregulated in lung tissue in an ALI animal model, and TLRs triggered macrophages, which contributed to the pathology and recovery of ALI by secreting proinflammatory or anti-inflammatory cytokines and phagocytosing apoptotic cells (26,27), indicating the important role of miR-155 in ALI. In an in vivo experiment, Worm et al (29) reported that pretreatment of miR-155 ASO could induce downregulation of G-CSF in splenocytes in LPS-induced murine inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, miR-155, a distinct miRNA molecule, was found to have an important role in inflammatory and immune response (17,19). Moreover, miR-155 also was found upregulated in lung tissue in an ALI animal model, and TLRs triggered macrophages, which contributed to the pathology and recovery of ALI by secreting proinflammatory or anti-inflammatory cytokines and phagocytosing apoptotic cells (26,27), indicating the important role of miR-155 in ALI. In an in vivo experiment, Worm et al (29) reported that pretreatment of miR-155 ASO could induce downregulation of G-CSF in splenocytes in LPS-induced murine inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Global miRNA profile analysis showed that the expression of miR-155 was elevated in ALI (21,23). Furthermore, miR-155 could regulate the transduction of TLRs signaling on mouse and human immune cells such as macrophages (24,25), *Department of Respiratory Medicine, East Hospital, Tongji University School of Medicine, Shanghai, China; which was critical for generation of proinflammatory cytokine storm and subsequently the development and recovery of ALI (26)(27)(28). Of interest, one report showed that pretreatment of antisense oligonucleotides (ASO) against miR-155 could lead to decreased expression of GM-CSF, which was an important pathogenetic factor in the pathology of ALI in LPS induced animal inflammatory disease (29).…”
mentioning
confidence: 99%
“…In contrast, alternately activated (M2) macrophages develop in response to IL-13 and IL-4, express arginase I, and promote tissue repair and restoration by secreting IL-10, TGF-b, and IL-6. 2,206 Comparable subsets have been suggested in cattle, although they have not been extensively characterized. 52 Thus, macrophages in the lung maintain alveolar homeostasis by recycling surfactant, phagocytose particulates including bacteria, generate reactive oxygen and nitrogen species, and secrete cytokines and proteases, yet the spectrum of these functions depends on the monocyte subpopulation from which they were derived, the method of recruitment, and the stimuli encountered in the lung microenvironment.…”
Section: Effects Of Predisposing Factors On Pulmonary Alveolar Macropmentioning
confidence: 99%
“…52 Thus, macrophages in the lung maintain alveolar homeostasis by recycling surfactant, phagocytose particulates including bacteria, generate reactive oxygen and nitrogen species, and secrete cytokines and proteases, yet the spectrum of these functions depends on the monocyte subpopulation from which they were derived, the method of recruitment, and the stimuli encountered in the lung microenvironment. 2,206 Most research on alveolar macrophages of cattle, particularly the effects of viral infection and corticosteroids, predated these concepts of macrophage heterogeneity, which are of considerable relevance to understanding the findings. For example, if viral infections elicit exudative macrophages, then macrophages isolated from infected calves would be expected to respond differently than normal resident macrophages infected in vitro, yet this difference would not represent a direct effect of viral infection on macrophage function.…”
Section: Effects Of Predisposing Factors On Pulmonary Alveolar Macropmentioning
confidence: 99%
“…Studies in experimental animals and clinical settings have led to the concept that alveolar macrophages (AMs) play a central role in the pathogenesis of COPD as a major source of mediators. 2,3 AMs are among the most abundant cells in the respiratory tract and are characterized by considerable diversity and plasticity in response to various signals within this environment. AMs undergo classical pro-inflammatory M1 activation, which is characterized by the expression of high levels of pro-inflammatory cytokines, high production of reactive nitrogen and oxygen intermediates, promotion of T helper-1 response, and strong tumoricidal and microbicidal activity.…”
Section: Introductionmentioning
confidence: 99%